In Silico Identification of Putative miRNAs Targeting GME to Increase Ascorbic Acid in Tomato - Bonnu, Christin H.; Tiara Ayu Nugraha Putri; Blegur, Ernes Josias (Biospecies, 2025)
The primary natural sources of ascorbic acid or vitamin C are fruits and vegetables, withtomatoes being one of the most readily available and accessible examples. The biosynthesisof ascorbic acid through the L-galactose pathway plays a key role in regulating vitamin C production in tomatoes. microRNAs (miRNAs) are among the various regulators that interact with mRNA involved in this process. Investigating how miRNA regulates mRNA could provide crucial information for developing genetic engineering techniques to boost vitamin C production. The main purpose of this research is to identify potential miRNA regulators ofGME using in silico approach. The research findings demonstrated that ascorbic acid biosynthesis in tomato involves 19 gene IDs. It also discovered that GME interacts with multiple miRNAs in tomatoes, specifically sly-miR-159b, sly-miR-159a, sly-miR-167, sly-miR-319c, sly-miR-319b and sly-miR-319a. Among these miRNAs, sly-miR-159a displays higher expression, which allows it to exert a suppressive effect on GME activity (negative regulator), leading to a decrease in vitamin C production. Decreasing the expression of this miRNA provides a potential molecular approach for enhancing the nutritional quality of tomato cultivars in response to the rising demand for functional foods.